Two new species of harvestmen (Opiliones, Eupnoi, Neopilionidae) from Waitomo, New Zealand - Taylor, Christopher; Probert, A. (Pensoft Publishers, 2014)
Two new species of harvestman (Opiliones: Neopilionidae: Enantiobuninae) are described from the Waitomo region of the North Island, New Zealand, Forsteropsalis bona sp. n. and F. photophaga sp. n. Both have been collected within caves in the region, where predation on glow-worms Arachnocampa luminosa has been previously recorded for one or both species (misidentified as ‘Megalopsalis tumida’). However, both are regarded as troglophiles rather than strict troglobites due to the presence of specimens outside the cave systems, and the absence of troglobitic adaptations. Megalopsalis tumida (Forster, 1944) is identified as a junior synonym of Forsteropsalis fabulosa (Phillipps & Grimmett, 1932).